Disaggregating Homicide: Changing Trends in Subtypes over Time - Skott, Sara (Criminal justice and behavior, 2019)
Due to the heterogeneity of homicide, certain subtypes of homicide might have remained stable or even increased over time in the overall context of decline. Adding to the research attempting to identify a standardized classification system of homicide, this study used a novel, sophisticated statistical approach (multilevel latent class analysis [MLCA]) and an inductive theoretical stance to identify subtypes of homicide in Scotland and to examine how these types have changed over time. Using variables relating to the victim, offender, and the incident of homicide, four between-level types with three within-level classes of offenders in each type were identified. The findings showed that while all homicide types demonstrated an absolute decrease, domestic homicides had demonstrated a relative increase over time. Implications for policy, theory, and practice are discussed.